KOMUNIKASI BISNIS PEMASARAN ONLINE (Proses dan Strategi Pemasaran Online Bagi Pelaku Bisnis di Kota Kupang) - Yermia Djefri Manafe (Universitas Nusa Cendana, 2016)
Business communication which is built in the online shop-reaching not only limited tocorrespondence and advertising that are likely to be persuasive, but also cover all aspects. Businesscommunication is done between humans, humans with institutions and institutions with aninstitution related to the exchange of goods or services for profit. Business communications covers allaspects of